A case study on impact transcendental communication on emotional well-being in Indonesia - Nursanti, Siti; TAyo, Yanti; Nirmala , Ine; Armen Gemael, Qorr (Jurnal Studi Komunikasi, 2025)
This study examined the impact of transcendental communication on the emotional well-being of older adults in Indonesia. Employing a case study approach within an elderly Islamic study group (pengajian), data were collected through in-depth interviews, focus group discussions (FGDs), and participatory observations involving productive older adults, health workers, and community leaders. The findings indicate that transcendental communication, including practices such as communal prayer, Quran memorisation, and in-depth dialogue, has a significantly positive effect on the emotional well-being of older adults. Participants who engaged in these practices reported reduced stress and anxiety, enhanced self-awareness, and greater optimism and inner calm. This study underscores the potential of transcendental communication as an effective strategy for enhancing the emotional well-being of older adults in Indonesia. It provides policy recommendations to support its broader implementation.